Cardiac Tamponade Due to Right Ventricle Perforation: A Rare Complication of Catheter Ablation for Ventricular Tachycardia Storm - Annisa Puspitasari Nachrowi; Simon Salim; Angga Pramudita; Muhammad Yamin (Acta Medica Indonesiana)
Cardiac tamponade is a rare but fatal complication of catheter ablation. We are reporting a case of a 73-year-old male with ventricular tachycardia (VT) storm undergoing urgent VT ablation, who was later found to have right ventricle (RV) perforation—an unusual site for catheter ablation complication. The patient underwent isochronal late activation mapping (ILAM)-based ablation and elimination of local abnormal ventricular activities (LAVA). After procedure, his blood pressure rapidly decreased, and he was found to have cardiac tamponade. The tamponade was recurring despite of pericardial pigtail placement; thus, the patient was prepared for open-heart surgery. To preserve blood, auto transfusion was used as a bridging therapy.